Development of human digestive organ media based on Assemblr EDU - Arnelia Dwi Yasa; Farida Nur Kumala; Rujian Nur Andi Alfianto; Moh Salimi (Himpunan Pengembang Kurikulum Indonesia (HIPKIN), 2024)
This study focuses on developing and evaluating a new learning media called Assemblr EDU-based human digestive organs media for elementary science learning. The motivation behind this research is the limitation of current learning materials, such as books and worksheets, which hinder students' understanding of the subject. The ADDIE development research model is employed, with 5th-grade students as the subjects. The study utilizes descriptive data analysis techniques and collects data through questionnaires using a Likert scale. The media is evaluated by material experts, media experts, linguists, teachers, and students. The results reveal that the media is considered feasible, with 88.5 percent of media experts rating it as